Modeling of Particle Formation in Arc Discharges by Monte-Carlo Based Population Balance Modeling. (7th February 2017) - Kotalczyk, Gregor; Skenderovic, Ivan; Kruis, Frank Einar
ABSTRACT: A simulation method is presented which encompasses all relevant mechanisms, which are necessary for the description of the early stages of particle formation in arc discharges. Next to discrete coagulation and nucleation events, a continuous surface growth process is included into the simulation, making thus the description of the evaporation of thermodynamic unstable particles possible. The driving force for the nucleation and growth/evaporation is coupled to the monomer concentration in the gaseous phase and thus subject to change in the further course of the simulation. It is shown, that the simulation results gained by the incorporation of all three of these processes cannot be reproduced, if one of those processes is not simulated.